Formułowanie strategii eksportowej przedsiębiorstwa - Otta, Wiesław J. (Wydział Prawa i Administracji UAM, 1989)
The article attempts to state the principles of formulating export strategy of an enterprise by its management. Formulating export strategy consists in making choices on the basis of a diagnosis of a strategic problem. The choices are concerned with: 1) a domain of export activity — what will the scope of export activity be? 2) a product — market portfolio — what products/services and for what markets will the enterprise export? 3) a programme of activity on target markets — in what way will the enterprise operate in selected markets? Further choices within the process of formulating export strategy are characterized by: 1) a gradual narrowing of objective scope and time limit of choice; 2) shifts in importance and form of criteria of choice — from general premises of adequacy to precisely defined criteria of efficiency. Each phase of choice comprises a set of steps preparing a decision and a process of taking a decision. A passage to further phases of choice is conditioned upon the outcome of a diagnosis of a strategic problem. This procedure is of iterative character — it is possible to return to a stage of diagnosis from a final step of any phase.
Principles of export strategy of an enterprise